2015
DOI: 10.1007/s10961-015-9412-0
|View full text |Cite
|
Sign up to set email alerts
|

Do graduated university incubator firms benefit from their relationship with university incubators?

Abstract: Business incubators have become a popular policy option and economic development intervention tool. However, recent research shows that incubated firms may not benefit significantly from their incubator relationships, and may even be more vulnerable to failure post departure (graduation) from an incubator. These findings suggest that the impact of business incubation on new venture viability may be contingent on the type of support offered by an incubator and attributes of business environments within which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 22 publications
2
76
1
3
Order By: Relevance
“…They find support for their hypotheses that a university link reduces probability of new venture failure, but retards the firm's graduation from the incubator. Lasrado et al (2016) investigate whether firms graduating from university incubators attain higher levels of post-incubation performance than firms participating in non-university affiliated incubators do. Results show that university incubated firms do indeed benefit from their relationship with university incubators.…”
Section: Incubators' Impact At the Level Of The New Firmmentioning
confidence: 99%
“…They find support for their hypotheses that a university link reduces probability of new venture failure, but retards the firm's graduation from the incubator. Lasrado et al (2016) investigate whether firms graduating from university incubators attain higher levels of post-incubation performance than firms participating in non-university affiliated incubators do. Results show that university incubated firms do indeed benefit from their relationship with university incubators.…”
Section: Incubators' Impact At the Level Of The New Firmmentioning
confidence: 99%
“…217). These resources matter, as Lasrado et al (2016) found university incubated firms outperformed a matched sample of non-university incubated firms in terms of employment and sales.…”
Section: Tenancy and Service Supportmentioning
confidence: 93%
“…New firms with greater access to network capital are better able to innovate and acquire knowledge through securing resources that enable them to develop and succeed (Aldrich et al , 1987Hoang & Antoncic 2003;Huggins & Thompson 2015;Tello et al 2012). ESOs such as incubators foster this access as membership provides new ventures with connectivity to other firms (Lasrado et al 2016) and act as a "mechanism for embedding the company in (entrepreneurial) networks" (Bøllingtoft 2012, pp. 304).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the key function of incubation being to assist future entrepreneurs in establishing their businesses, post-incubation success is not a given (Mas-Verdú et al, 2015). Recent research has suggested that incubated firms may not benefit considerably from their relationship with their incubators and may even become more vulnerable to failure after graduation (Lasrado et al, 2016).…”
Section: Post-incubationmentioning
confidence: 99%